2015
DOI: 10.3390/ejihpe5020023
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional social support in elderly objective and subjective health ratings

Abstract: This paper aims to investigate the causes that explain the discrepancies between the effects of social relationships on health and wellness of the elderly people. Several disciplines of health sciences have developed different theories to explain the evidence that confirm the positive effects of social relations. Furthermore, there is acumuative evidence confirming most of the predictions derived from its principles. However, the empirical evidence has not always confirmed these beneficial relationships and so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…The widely varied measures of social support used in previous studies could make comparison with the present report difficult. However, previous reports had reported low ( Bai et al, 2018 ) and high ( Iglesias & Arias, 2015 ) levels of social support among older adults. The fact that the setting of the present study practice extended family setting where the family members have a filial responsibility of taking care of their old or sick relatives might explain the high level of social support recorded in this study ( Okoye et al, 2019 ).…”
Section: Discussionmentioning
confidence: 89%
“…The widely varied measures of social support used in previous studies could make comparison with the present report difficult. However, previous reports had reported low ( Bai et al, 2018 ) and high ( Iglesias & Arias, 2015 ) levels of social support among older adults. The fact that the setting of the present study practice extended family setting where the family members have a filial responsibility of taking care of their old or sick relatives might explain the high level of social support recorded in this study ( Okoye et al, 2019 ).…”
Section: Discussionmentioning
confidence: 89%
“…27 31 It is noteworthy that specific dimensions of supportive function referring to both of quantitative and qualitative aspects depict beneficial roles on health as personal resources in different stress life events. 31 Veiel pointed out that types of available support should be included in the social support assessment. 32 In addition, Wills and Shinar depicted the dimensions of available support or functional support relating to social support intervention in terms of emotional support, instrumental support, informational support, companionship support and validation which provide specific theoretically expected benefits for coping efforts.…”
Section: Open Accessmentioning
confidence: 99%
“…Stephan et al [59] found that both formal and informal support systems play active roles in providing the resources with which SEIs are 'forged'. However, informal support (support from family, friends, and acquaintances) could provide inimitable resources that have far reaching effects on entrepreneurial intent than formal (government) support [12,61]. In fact, Greve and Salaff [62] found that an entrepreneur's social network plays different roles at each stage of the entrepreneurial journey, but most especially at the planning stage.…”
Section: Ss and Seismentioning
confidence: 99%